ECO-PHYSIOLOGICAL AND CONSERVATION STUDIES ON VERNONIA AMYGALINA IN EKITI STATE, NIGERIA (Biological Sciences - PJSIR, 2004)
The study examined some aspects of the ecology, physiology, utilization and conservation of Vernonia amygalina. The seeds were found to be positively photoplastic with a pre-exposure time of 20 min to illumination required for its optimum germination. The seeds thrive well in slightly acidic soils with low organic matter and high water holding capacity. These characteristics suggest that the species could easily be cultivated in the area studied. The ethnobotanical uses of the species were valued against some socio-economic features of respondents in the study area. These include household size, farm size holdings, educational and economic status of the communities. Results obtained revealed that these features were not regarded as pre-requisites to the consciousness of the respondents to the utilization of this plant. At present, households’ homesteads and farms constituted the major primary and secondary sources of the species to the respondents, respectively. The relative abundance test carried out at these sources, however, indicated that the species were of rare occurrence in the locality, hence it is presently endangered in the study area. The need for its conservation was considered as inevitable. Strategies toward the attainment of this goal were proposed.